Longitudinal changes in pelvic floor muscle strength among parous women - Myer, Emily N. B. (Am J Obstet Gynecol, 2018)
BACKGROUND: There is limited knowledge of the effects of time on change in pelvic floor muscle strength after childbirth. OBJECTIVE: The objectives of this study were to estimate the change in pelvic floor muscle strength in parous women over time and to identify maternal and obstetric characteristics associated with the rate of change. STUDY DESIGN: This is an institutional review board-approved prospective cohort study of parous women. Participants were recruited 5—10 years after first delivery and followed annually. Pelvic floor muscle strength (peak pressure with voluntary contraction) was measured at 2 annual visits approximately 4 years apart with the use of a perineometer. We calculated the change in peak pressures, which were standardized per 5-year interval. Linear regression was used to identify maternal and obstetric characteristics that are associated with the rate of change in peak pressure. The obstetric variable of greatest interest was delivery group. Participants were classified into 3 delivery groups (considering all deliveries for each multiparous woman). Delivery categories included cesarean only, at least 1 vaginal birth but no forceps-assisted deliveries, and at least 1 forceps-assisted vaginal birth. Statistical analysis was completed with statistical software. RESULTS: Five hundred forty-three participants completed 2 perineometer measurements with a median 4 years between measures (interquartile range, 3.1—4.8). At initial measurement, women were, on average, 40 years old and 8 years from first delivery. Initial strength was higher in participants who delivered all their children by cesarean (38.5 cm H(2)O) as compared with women with any vaginal non-forceps delivery (26.0 cm H(2)O) or vaginal forceps delivery (13.5 cm H(2)O; P<.001). There was a strong correlation between the first and second perineometry measurement (r=0.84). Median change in pelvic floor muscle strength was small at 1.2 cm H(2)O per 5 years (interquartile range, −5.6, 9.9 cm H(2)O). In multivariable analysis, women who delivered by cesarean only demonstrated almost no change in strength over 5 years (0.2 increase cm H(2)O per 5 years); those who experienced at least 1 vaginal or vacuum delivery increased strength (4.8 cm H(2)O per 5 years) as did women with at least 1 forceps delivery (5.0 cm H(2)O per 5 years). Additionally, obese women had a significant reduction in strength (−3.1 cm H(2)O per 5 years) compared with normal weight participants (0.2 cm H(2)O per 5 years). CONCLUSION: Among parous women, pelvic muscle strength increased minimally over time with an average change of 1.2 cm H(2)O per 5 years; change in strength was associated with mode of delivery and obesity.